2018
DOI: 10.1111/jonm.12713
|View full text |Cite
|
Sign up to set email alerts
|

The meanings of the unlicensed assistive personnel role in nursing homes: A triadic job analysis perspective

Abstract: The study takes a step forward toward better defining the professional boundaries delineating the meaning of the UAP position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…These findings support the rationale behind Müller et al, (2018) inquiry into RACF care which made the RN-GP professional collaboration its focus, and adds significance to our subsequent finding that interruptions to continuity of care damage this interaction. They also add international support to Müller et al While it has been reported that the care staff or nursing assistant (NA) role is important and includes notifying the RN of physical or behavioural changes (Band-Winterstein et al, 2019), and that resident care outcomes are positively associated with NA hours and years of experience in the current facility (Boscart et al,2018), this view of RACF care staff contributing their assessments to inform care planning and providing excellent care has not been, to our knowledge, previously reported. However, this is consistent with the value attributed to community-based family carers' contribution (Wong-Cornall et al,2017).…”
Section: Discussionmentioning
confidence: 87%
“…These findings support the rationale behind Müller et al, (2018) inquiry into RACF care which made the RN-GP professional collaboration its focus, and adds significance to our subsequent finding that interruptions to continuity of care damage this interaction. They also add international support to Müller et al While it has been reported that the care staff or nursing assistant (NA) role is important and includes notifying the RN of physical or behavioural changes (Band-Winterstein et al, 2019), and that resident care outcomes are positively associated with NA hours and years of experience in the current facility (Boscart et al,2018), this view of RACF care staff contributing their assessments to inform care planning and providing excellent care has not been, to our knowledge, previously reported. However, this is consistent with the value attributed to community-based family carers' contribution (Wong-Cornall et al,2017).…”
Section: Discussionmentioning
confidence: 87%
“…The sample sizes in the 36 qualitative studies were generally small (30 study participants or fewer) and only two studies included sample sizes of more than 80 CGs and OPs [ 52 , 61 ]. The search strategy was challenging because the construct caregiver was used inconsistently and interchangeably with nurses, nurse-aides, care managers, and other healthcare workers [ 18 , 19 , 27 , 51 53 , 57 59 , 62 , 63 , 66 , 69 ]. The exclusion criteria for OPs did not distinguish between mild and severe cognitive impairment, and as a result some studies could have been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of CGs, studies include the meanings associated with the role of caregiving [49][50][51][52][53]; communication strategies in caregiving [54][55][56]; and the competence of CGs [57,58]. Studies focusing on the care relationship both from OPs' and CGs' perspectives include the requirements to perform caregiving [59]; the meaning of care [60][61][62]; the effects of ethnic differences [63]; beliefs about and assumptions about care [64]; and the social needs of OPs [65]. A few studies explored the care relationship in long-term care from multiple perspectives, including family members and staff [66][67][68][69].…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation